Web-Based Solar Powered Automated Hydroponics System using WEMOS Technology - Gamboa, John Carlo L.; Vicente, Clarissa P.; Santos, Rowell C.; Tamayo, Josan D. (Future Science / FSH-PH Publications, 2026)
This study aimed to develop a Web-Based Solar-Powered Automated Hydroponics System. Further, it aimed to evaluate its technical performance. The device used WeMos technology, gathering feedback from agriculturists and farmers. It used a solar panel with the following specifications Peak Power (Pmax): 100W, Open Circuit Voltage (Voc): 21.6V, Short Circuit Current (Isc): 6.1A, Maximum Power Voltage (Vmp): 18V, Maximum Power Current (Imp): 5.56A, and Temperature Coefficient: -0.45%/°C. Agriculturists unanimously provided a perfect mean score of 5.00 across all technical aspects, indicating complete consensus and a strong endorsement of the system's capabilities. While farmers satisfaction overall mean score is 4.60. The farmers' perceptions showed slightly more variability than the agriculturists. The combined assessment from both groups was consistent with the individual results. The system's monitoring capability received the highest combined score, while report generation and ease of use received the lowest, though all scores were positive. The study underscored the capability of its Web-Based Solar-Powered Automated Hydroponics System as a promising instrument to advance modern agricultural practices and address the challenges of food production sustainably. Based on the findings of the study and to further enhance the Web-Based Solar-Powered Automated Hydroponics System, the following recommendations for additional features may be considered Advanced-Data Analytics, Integration with IoT Sensors, Mobile Application, and Comparative Analysis.